Modeling the Invasion of Holly (Ilex aquifolium): Spatial Relationships and Spread Trajectories. Issue 3 (2nd July 2016) - López, Santiago; Stokes, David L.
Abstract : In this study, we investigated the environmental factors associated with the establishment of invasive English holly ( Ilex aquifolium ) and the spatiotemporal trajectories of its potential spread. We collected georeferenced presence and absence and demographic data of holly between 2011 and 2014 in Saint Edward State Park, Washington. We analyzed them through a spatially explicit framework that combines multiple logistic regression, cellular automata, and bivariate quadratic modeling. Results showed that the presence of holly is influenced by the proximity to evergreen coniferous vegetation and forest edge, distance to streams, forest structure, and slope direction. Our study confirmed that local environmental conditions, species characteristics, and vegetative and dispersal mechanisms play a significant role in determining the rate and success of holly establishment across the different phases of invasion. Invasive species management plans should consider both species characteristics and their habitat and the interactions among them when planning long-term strategies for control and eradication.